MECHANISM AND KINETIC OF RECRYSTALLIZATION AND PRECIPITATION IN Al-30 wt. %Zn ALLOY - BENSAADA, S.; BOUZIANE, M.T. (Science des matériaux (Laboratoire LARHYSS), 2016)
In this contribution, it has been studied effect of degree of cold plastic deformation on occurrence of recrystallization and precipitation reaction in Al-30wt%Zn alloy, during isothermal annealing. It has been observed, that the mechanism and kinetics of these two reactions depend mainly on this mechanical parameter. For this investigation, different techniques were used; optical microscopy, hardness measurements and X-ray diffraction. Key-words: precipitation -recrystallization - deformation- grain- boundary